find the product of this(x-1) (x 2)

Question

Asked 2/15/2012 10:02:12 PM

Updated 9/10/2014 1:20:25 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [9/10/2014 1:20:25 AM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

thederby|Points 859|

thederby|Points 859|

Expert answered|Envious|Points 30|

Question

Asked 2/15/2012 10:02:12 PM

Updated 9/10/2014 1:20:25 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [9/10/2014 1:20:25 AM]

Rating

8

(x - 1)(x + 2)

= x^2 + 2x - x - 2

= x^2 + x - 2

= x^2 + 2x - x - 2

= x^2 + x - 2

Added 9/10/2014 1:19:06 AM

This answer has been confirmed as correct and helpful.

8

(9 - 5x)^2

= (-5x + 9)(-5x + 9)

= 25x^2 - 45x - 45x + 81

= 25x^2 - 90x + 81

= (-5x + 9)(-5x + 9)

= 25x^2 - 45x - 45x + 81

= 25x^2 - 90x + 81

Added 9/10/2014 1:20:18 AM

This answer has been confirmed as correct and helpful.

5

(x-1)(x+2) using the foil method, we get x^2+2x-x-2

=x^2-x-2

And for the (9-5x)^2, the expanded form would be 25x^2-90x+81.

=x^2-x-2

And for the (9-5x)^2, the expanded form would be 25x^2-90x+81.

Added 2/15/2012 10:42:42 PM

This answer has been flagged as incorrect.

Flagged by andrewpallarca [9/10/2014 1:19:08 AM]

38,689,904

questions answered

There are no comments.